A single-center experience of home parenteral nutrition for pediatric intestinal failure - Hwang, Honam; Ko, Dayoung; Yang, Hee-Beom; Youn, Joong Kee; Moon, Jin Soo; Ko, Jae Sung; Kim, Hyun-Young (Frontiers in Pediatrics, 2025)
BackgroundIntestinal failure (IF) in pediatric patients often necessitates home parenteral nutrition (HPN) as a life-saving therapy. While global HPN programs are well-established, data specific to South Korea remain scarce. This study aimed to report the experience with pediatric HPN at a single center in Korea.MethodsThis retrospective study included 40 pediatric patients receiving HPN between 2009 and 2021 at Seoul National University Children's Hospital. The following data of patients were collected: demographics, diagnoses, surgical factors, HPN protocols, complications including catheter-related bloodstream infection (CRBSI), intestinal failure-associated liver disease (IFALD), hospitalization records, and growth outcomes.ResultsForty pediatric patients with IF were followed for a median of 53.5 months. Common IF causes included chronic intestinal pseudo-obstruction syndrome (45.0%) and short bowel syndrome (22.5%). Six (15.0%) patients were weaned off HPN. Complications included CRBSI (60.0%, 0.90/1,000 catheter days) and metabolic issues such as IFALD (45.0%). Growth outcomes were suboptimal, with declining z-scores for weight and weight-for-height during the HPN period. No mortality was reported during the study period.ConclusionThis study provides insights into the experiences of pediatric HPN in a single center in Korea, with favorable survival and complication outcomes. However, low weaning rates and suboptimal growth outcomes highlight the need for systemic improvements including enhanced logistical support, legal reforms, and tailored nutritional strategies to optimize care for pediatric HPN patients in Korea.